PEMANFAATAN DIGITAL MARKETING, PEMASARAN YANG EFEKTIF OLEH PESERTA DIDIK SMK AL-MANAR, CIBENTANG KECAMATAN CISEENG, KABUPATEN BOGOR - Cornelia Dumarya Manik; Theobaldus Boro Tura; Agus Agus (Jurnal Pengabdian Sosial, 2023)
ABSTRACT The purpose of implementing this community service is to help students in promoting the products of the position of Al-Manar School in Al-Manar on Jl. Amd Cibentang No.184, Cibentang, Ciseeng, Bogor has a lot of potential and products produced by the community. Students of Al-Manar School do conventional marketing of their products and have not done product marketing through digital marketing. This community service activity aims to:  Providing insight into the concept of digital marketing and technological products used for product marketing, , providing training and simulation on the use of digital media in product marketing, compiling effective persuasive messages, and providing solutions to realize al-Manar School students to promote products through digital media. This method of community service activities begins with the preparatory stage and field surveys. This survey phase begins with a direct discussion with SMK students in Ciseeng Village, Ciseeng District, Bogor Regency to identify the needs, opportunities, and challenges faced by al-Manar School students. Then, the socialization and training stage is carried out by the team. At this stage there are five things implemented by the service team Namely (1) Explaining How to Use Digital marketing and Marketing more effectively Interestingly, (2) finding a strategic location for students (3) creating promotional content that is easy for students to remember (4). And how to distribute the product so that it can get to the customer. (5). Online Marketing. The results of this community service activity are as follows: Students' knowledge in this case students of SMK Al- Mahar Ciseeng, Kec Ciseeng, Bogor Regency regarding marketing management before Pkm activities are mostly in the category of not understanding. After the PKM activity was carried out and the presentation of the material was delivered, it was known that the participants' knowledge of marketing management after it was delivered increased. Keywords: Digital marketing, effective marketing